DEVELOPMENT OF AN APPLICATION FOR THE THERMAL TREATMENT OF OIL SLIME TO PREVENT ENVIRONMENTAL POLLUTION IN THE INDUSTRIAL OIL AND GAS SECTOR - Balakayeva Г.Т.; Kalmenova Г.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
Oil refining and production activities of oil and gas-producing enterprises necessarily have an anthropogenic impact on the environment, therefore, environmental issues and rational use of natural resources are important. The most dangerous pollutants of all components in the natural environment are oil waste, and one of the most effective processing methods is heat treatment. The task was set to neutralize oil waste by heat treatment of oil sludge. Research is carried out by methods of mathematical and numerical modeling of heat treatment, the results of which characterize the change in temperature and mass of the stream over time. Numerical modeling is carried out by the method of using alternating directions in a hidden iterative scheme until the convergence condition is met. The purpose of this work is to create an application for solving scientific and practical problems of oil waste treatment. The application used allows you to solve the problems of oil sludge processing. With the help of color-animated illustrations and a graphical interface, the results are visualized and provide the possibility of interactive interaction with the user.